In situ synthesis of nitrogen- and sulfur-enriched hierarchical porous carbon for high-performance supercapacitor - Mehare, Rupali S.; Ranganath, Suresha P.; Chaturvedi, Vikash; Badiger, Manohar. V.; Shelke, Manjusha V. (Energy & Fuels, 2018)
In this work, we present a simple and facile method for the nitrogen (N)- and sulfur (S)- doped porous three-dimensional (3D) spongelike carbon materials via direct pyrolysis of N and S containing polymer N,N'-methylene-bis-acrylamide cross-linked poly(acrylamide-co-2-acrylamido-2-methyl-1-propanesulfonic acid) at varying temperatures under inert atmosphere. The obtained nitrogen- and sulfur-doped porous carbons (NSPCs) possess 3D hierarchical porous structure and contain a significantly high amount of N and S species. The concurrent incorporation of N and S successfully modified the surface properties of carbon materials and lead to enhanced capacitive performance. The presented NSPC exhibits specific capacitance of 230 F g(-1) at a current density of 1 A g(-1) and showed excellent cycling stability, depicting a promising material for energy storage devices.